Permafrost-Glacial Evolution during the Holocene in the Italian Central Alps - GUGLIELMIN M.; DRAMIS F.; CANNONE, Nicoletta (2001)
This paper discusses the Holocene evolution of two sites in the Italian Central Alps, the Foscagno Valley and the Stelvio-Livrio area, in terms of the interaction between permafrost distribution and glacial history. The applicability of phytosociological vegetation survey to investigate recent glacial evolution where geomorphological evidence is poor or totally absent is also illustrated. Bottom temperature of snow measurements and detailed geomorphologic survey and air-photo interpretation were carried out in the Stelvio-Livrio area. Boreholes were drilled in each site, one (24 m deep) in the Foscagno rock glacier (2510 m asl), the second (100.3 m deep) in dolostone-limestone bedrock at the Stelvio Pass (3000 m asl). The latter borehole is a component of the PACE European Permafrost Monitoring Network. In the Foscagno Valley, the formation of permafrost during a cold and dry phase of the Holocene allowed the preservation of an ice body which otherwise would have been disappeared. More recently, a Little Ice Age glacier advance, whose exact location and extension were defined by means of the analysis of vegetal associations, induced some degradation in the permafrost. In the Stelvio-Livrio area, a cold-based glacier apparently had much less influence on the local permafrost evolution and thermal regime.